18F‐FPEB PET/CT Shows mGluR5 Upregulation in Parkinson's Disease. Issue 1 (19th September 2018) - Kang, Yeona; Henchcliffe, Claire; Verma, Ajay; Vallabhajosula, Shankar; He, Bin; Kothari, Paresh J.; Pryor, Kane O.; Mozley, P. David
ABSTRACT: BACKGROUND AND PURPOSE: Dopamine and glutamate reciprocally regulate each other in some of the neurocircuits affected by Parkinson's disease (PD). The objective of this pilot study was to explore relationships between these neurotransmitter systems with positron emission tomography. METHODS: The sample consisted of nine patients with PD and eight healthy volunteers (HVs). Dynamic images of the brain were acquired after the IV administration of ∼370 MBq (10 mCi) of [ 11 C]PE2i, a dopamine transporter (DaT) imaging agent, and ∼185 MBq (∼5 mCi) of [ 18 F]FPEB, a selective metabotropic glutamate receptor 5 (mGluR5) antagonist. Multiple volumes of interest were semiautomatically placed on contemporaneously acquired MRI scans. Nondisplaceable binding potentials (BPND ) were calculated with the Logan reference tissue model using cerebellar white matter as the reference region. RESULTS: The findings showed that average [ 18 F]FPEB BPND values were slightly more than 20% higher in PD than HVs in several mesocortical regions, including the bilateral putamen ( P = .01), hippocampus ( P = .02), and amygdala ( P = .05). Average [ 11 C]PE2i BPND was significantly reduced by about half or more in patients with PD in the bilateral caudate ( P < .001) and putamen ( P < .001). CONCLUSIONS: mGluR5 seems upregulated in strategic dopaminergic brain regions adversely affected by PD. The findings seem to confirm that DaT tracers are better discriminatory biomarkers for diagnosing PD; however, mGluR5 tracers might deserve further exploration as potential biomarkers of response in clinical trials.